Within-week and between-week variability of external and internal load demands of professional male volleyball players - Ricardo Lima; Francisco Tomás González Fernandez; Joel Pereira; Lorenzo Laporta; Henrique Castro; André Rebelo; Ana Filipa Silva; Sérgio Matos; Filipe Manuel Clemente (Termedia Publishing House, 2023)
Purpose The aim of the present study was to analyse the within-week variations according to the internal (rate of perceived exertion [RPE], and session-RPE) and external (jump height average, minimum jump, maximal jump, range of jump, number of jumps and density) intensity. Methods Twelve male elite/international volleyball athletes from the Portuguese 1st division (age: 21.7 ± 4.19 years of age; experience: 6.2 ± 3.8 years; body mass: 85.7 ± 8.69 kg; height: 192.4 ± 6.25 cm; body mass index: 23.1 ± 1.40 kg/m 2 ) participated in this study. The players were monitored over 26 microcycles, 101 training sessions, and 20 matches. To assess the workload, the CR10 Borg scale and an inertial measurement unit (IMU) were used. Results According to the internal workload, RPE revealed significant differences between MD-4 and MD-2, MD-4 and MD1, MD-3 and MD-1, and MD-2 and MD-1 ( p < 0.05). In the same line, session RPE showed significant differences between MD-4 and MD-2, MD-4 and MD-1, MD-3 and MD-2, MD-3 and MD-1, and MD-2 and MD-1 ( p < 0.05). On the other hand, the external load demands revealed statistical differences regarding the number of jumps (MD-4 and MD-2, MD-4 and MD-1, MD-3 and MD-1, and MD-2 and MD-1) and the density of the training sessions (MD-4 and MD-1, and MD-2 and MD-1). Conclusions The primary findings of this study suggest that higher-intensity training sessions tend to occur during the middle of the week, with a tapering effect observed as the competition date approaches.